2009
DOI: 10.1080/13668250802690914
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of parenting stress among Vietnamese mothers of young children with and without cognitive delay

Abstract: Special education and early intervention services should be developed and available to educate the children with cognitive delay and support their mothers in Vietnam. Effective services also need to address their poverty and health care needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…The impact of affiliate stigma on subjective burden and psychological well-being of caregivers, and the mediating influence of subjective burden According to the stress, appraisal and coping model, stressors such as affiliate stigma have the potential to impact caregivers' subjective burden significantly, such that the higher the stigma, the higher the subjective burden (Green 2003(Green , 2007Chou et al 2009;Shin & Nhan 2009;Werner et al 2012). Further, research shows the negative association between stigma and psychological well-being of caregivers.…”
Section: Stigma Of Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of affiliate stigma on subjective burden and psychological well-being of caregivers, and the mediating influence of subjective burden According to the stress, appraisal and coping model, stressors such as affiliate stigma have the potential to impact caregivers' subjective burden significantly, such that the higher the stigma, the higher the subjective burden (Green 2003(Green , 2007Chou et al 2009;Shin & Nhan 2009;Werner et al 2012). Further, research shows the negative association between stigma and psychological well-being of caregivers.…”
Section: Stigma Of Disabilitymentioning
confidence: 99%
“…According to the stress, appraisal and coping model, stressors such as affiliate stigma have the potential to impact caregivers’ subjective burden significantly, such that the higher the stigma, the higher the subjective burden (Green , ; Chou et al . ; Shin & Nhan ; Werner et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many studies have shed light on a variety of mechanisms through which maternal education may improve child health and development outcomes. For example, studies have found that more educated mothers make greater investments in child health promoting activities4; provide more learning opportunities for the child5; demonstrate higher quality interactions with their children6; possess greater knowledge about child health and development7 8 and experience less parenting stress 9…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis also showed that parenting stress of parents of children with ASD or DD were higher, even when compared to parents of children with other clinical diagnosis [10]. Furthermore, a study in Vietnam found having a child with cognitive delay was the strongest predictor of maternal stress [11].…”
Section: Introductionmentioning
confidence: 95%